A Comparison of Refractive Accuracy Between Conventional and Femtosecond Laser Cataract Surgery Techniques Using Modern IOL Formulas - Connell BJ (Dove Medical Press, 2021)
Benjamin J Connell,1,2 Jack X Kane,2 Rasik B Vajpayee2– 4 1Eye Surgery Associates, Melbourne, Victoria, Australia; 2Corneal Unit, Royal Victorian Eye and Ear Hospital, Melbourne, Victoria, Australia; 3Centre for Eye Research Australia, University of Melbourne, Melbourne, Victoria, Australia; 4Vision Eye Institute, Melbourne, Victoria, AustraliaCorrespondence: Benjamin J ConnellEye Surgery Associates, 2/232 Victoria Pde, East Melbourne, VIC, 3002, AustraliaTel +61 9416 0695Fax +61 9416 1816Email benconnell@outlook.com.auPurpose: To compare the refractive outcome prediction accuracy between conventional (CCS) and femtosecond laser assisted (FLACS) cataract surgery techniques using optimized lens constants for modern intraocular lens (IOL) formulas.Patients and Methods: Our retrospective, comparative, interventional case series, compared data from 196 eyes undergoing CCS and 456 eyes undergoing FLACS with Acrysof IOL (Alcon laboratories, Inc) implantation. After optimizing IOL constants, the predicted refractive outcome was calculated for all formulas for each case. This was compared to the actual refractive outcome to provide the prediction error. The performance of CCS and FLACS was compared by the absolute prediction error and percentage of eyes within 0.25D, 0.5D and 1.0D of anticipated refractive outcome.Results: There was no statistically significant difference in median absolute error between the CCS and LACS groups for the Kane (0.256, 0.236; p=0.389), SRK T (0.298, 0.302, p=0.910), Holladay (0.312, 0.275; p=0.090), Hoffer Q (0.314, 0.289; p=0.330), Haigis (0.309, 0.258; p=0.177), Barrett Universal 2(0.250, 0.250; p=0.866), Holladay 2 (0.250, 0.258; p=0.860) and Olsen (0.260, 0.255; p=0.570) formulas. Similarly, there was no consistent difference between the two techniques for percentage of patients within 0.25, 0.50 and 1.0D of predicted refractive outcome for each formula.Conclusion: There was no difference in refractive outcome prediction accuracy between the CCS and FLACS techniques.Keywords: femtosecond laser-assisted cataract surgery, refractive predictability, IOL formulas